Yugoslav diplomats during the interwar period - Micic, Srdjan (Balcanica Posnaniensia. Acta et studia, 2019)
The article deals with influence of the Serbian elite in the scope of the Yugoslav Foreign Service during 1918–1939. The influence of the elite circles was particularly prominent in the Yugoslav Army and in the Ministry of Foreign Affairs, as was the case in Serbia until 1918. As non-institutional factors had great influence on the work of state institutions, the first aim of this paper is to examine the main aspect for selection, career development and obstacles in the life of Yugoslav Diplomats, derived from the power struggle among elite circles. The second aim is to compare Serbian and Yugoslav experiences in order to establish similarities and differences in the characteristics of the pre-War and Interwar Diplomatic-Consular personnel. The analysis is based on Yugoslav archival materials, as well as on foreign published documents, memorial literature and relevant Yugoslav/Serbian and foreign historiography.